2009
DOI: 10.1007/s11695-009-9980-x
|View full text |Cite
|
Sign up to set email alerts
|

The Incapacity of the Surgeon to Identify NASH in Bariatric Surgery Makes Biopsy Mandatory

Abstract: No predictor of NASH was found. Surgeons' evaluation could not identify NASH individuals. Routine liver biopsy during bariatric operations is mandatory to differentiate NASH and nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
1
20
0
2
Order By: Relevance
“…Surgeons' evaluations could not identify NASH individuals. Teixeira et al [17] demonstrated the inability of surgeons to identify NASH by intraoperative liver appearance, ultrasound or lab findings. Routine liver biopsy during bariatric operations is mandatory to differentiate NASH and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons' evaluations could not identify NASH individuals. Teixeira et al [17] demonstrated the inability of surgeons to identify NASH by intraoperative liver appearance, ultrasound or lab findings. Routine liver biopsy during bariatric operations is mandatory to differentiate NASH and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 20% of NAFLD have positive serologies for antinuclear antibody, antismooth muscle antibody, and/or antimitochondrial antibody [36][37][38] ; therefore, liver biopsy evaluation might be the only means of determining the underlying cause of the disease. Furthermore, surgeons have shown that intraoperative visualization is commonly not correct for the prediction of either steatosis or advanced fibrosis, and thus liver biopsy is currently being recommended in the morbidly obese bariatric population at the time of surgery [39] . The final "pro" of liver biopsy is both confirmation of the diagnosis, as well as evaluation and semiquantitation of necroinflammatory lesions and fibrosis, and evaluation of architectural remodeling.…”
Section: Value Of Liver Biopsy Evaluation In Nonalcoholic Fatty Livermentioning
confidence: 99%
“…36 The measure of insulin sensitivity indices has shown a reduced mean insulin sensitivity in nonobese, non-diabetic young subjects with NASH in association with the different components of the metabolic syndrome.…”
Section: Insulin Resistancementioning
confidence: 99%